Pengaruh Produk Hijau terhadap Keputusan Pembelian Produk Lampu - M. Najib Zakariya; Didit Darmawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research examines how Green Products influence consumer decisions in purchasing energy-saving lighting products. Green Products Refer to products that do not endanger human health and are friendly to the environment, production processes that are efficient in using resources, produce minimal waste, and reducing negative impacts on the environment are the main focus in developing environmentally friendly products. Environmentally friendly products that offer value added without sacrificing quality compared to conventional products tends to attract more consumer attention. The widespread adoption of eco-friendly products can be linked to affordability, environmental harm, and energy efficiency, in addition to the ability to reduce harmful environmental impacts. This phenomenon is explored through a comprehensive understanding of the scientific literature, using a systematic methodology to synthesize the findings. The analysis shows that consumer purchasing behavior is strongly shaped by environmentally friendly product attributes. This study seeks to uncover the factors that drive this relationship, in addition to summarizing and interpreting the results of previous research on how environmentally friendly products influence lighting purchasing decisions.